ANALYSIS OF ECONOMIC GROWTH IMPACT ON THE PHENOMENON OF RURAL–URBAN MIGRATION AT JAVA ISLAND - Ridhowati; Nurlaela (CV. Radja Publika, 2026)
Urbanization represents a major phenomenon in the trajectory of economic development, particularly in developing economies. Over the last two decades, Indonesia has experienced a considerable rise in the proportion of people living in urban areas, especially on the island of Java, which serves as the core of the country’s economic activities. This research aims to examine the effect of regional economic growth on rural–urban migration within Java. A quantitative research design was applied using panel data regression covering six provinces at Java during the period 2015–2024. The study analyzed several variables, including regional economic growth, open unemployment rate, and average years of schooling, while income inequality was incorporated as a control variable affecting migration from rural to urban areas. Secondary data were collected from official publications of the Central Bureau of Statistics and processed using a panel regression approach with the Fixed Effect Model (FEM). The empirical results reveal that economic growth significantly and positively affects rural–urban migration in Java. Educational attainment also contributes positively to population mobility, whereas unemployment demonstrates a negative relationship with migration flows to urban regions. These findings suggest that the concentration of economic activities in urban centers acts as a strong pull factor for labor originating from rural areas. Consequently, policies promoting more balanced regional development are necessary to mitigate excessive urbanization pressure in major cities across Java.